Analysis of Customer Satisfaction Based on Atmosphere, Employee Attitude, Technology Services, Product Quality, Satisfaction and Loyalty at Culminers Coffee - Pratama, Safira Yunita; Muh Nur Ilham Y.A; Beril Kalalo; Andi Muhammad Zulfikar; Carolina Novi Mustikarini (Accounting Profession Journal (APAJI), 2025)
This study aims to analyze the influence of atmosphere, employee attitudes, technology services, and product quality on customer satisfaction, and to determine the relationship between customer satisfaction and customer loyalty. In this study, Culminers Coffee was chosen as the research location to facilitate sampling due to our distance. This study uses a quantitative method with a survey technique by distributing questionnaires to 238 Culminers Coffee consumers with the SEM PLS 4 analysis tool. The results of the analysis show that coffee quality, technology services, employee attitudes, and atmosphere have a significant influence on customer loyalty. However, customer satisfaction does not have a direct relationship to loyalty, which indicates that factors other than satisfaction play a greater role in building customer loyalty.